Layer‐by‐Layer Controlled Perovskite Nanocomposite Thin Films for Piezoelectric Nanogenerators. (18th August 2014) - Kim, Younghoon; Lee, Keun Young; Hwang, Sun Kak; Park, Cheolmin; Kim, Sang‐Woo; Cho, Jinhan
<x xml:space="preserve">Abstract</x> Perovskite nanoparticle‐based nanocomposite thin films strictly tailored using unconventional layer‐by‐layer (LbL) assembly in organic media for piezoelectric nanogenerators (NGs) are demonstrated. By employing sub‐20‐nm BaTiO3 nanoparticles stabilized by oleic acid ligands (i.e., OA‐BTONPs) and carboxylic acid (COOH)‐functionalized polymers, such as poly(acrylic acid) (PAA), the resulting OA‐BTONP/PAA nanocomposite multilayers are prepared by exploiting the high affinity between the COOH groups of PAA and the BTONPs. The ferroelectric and piezoelectric performance of the (PAA/OA‐BTONP)n thin films can be precisely controlled by altering the bilayer number, inserted polymer type, and OA‐BTONP size. It is found that the LbL assembly in nonpolar solvent media can effectively increase the quantity of adsorbed OA‐BTONPs, resulting in the dramatic enhancement of electric power output from the piezoelectric NGs. Furthermore, very low leakage currents are detected from the (PAA/OA‐BTONP)n thin films for obtaining highly reliable power‐generating performance of piezoelectric NGs.